Sistem Monitoring Kebocoran Gas Berbahaya di Lingkungan Kawasan Industri berbasis Bluetooth Low Energy (BLE) - Bambang Gunadi; Nurul Hidayat; Arief Andy Soebroto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Some factories have been using gas as a source of combustion fuel for production purposes, resulting in emissions from the combustion process. Most of the gas used for the fuel source consists of methane gas or CH4. Meanwhile, emissions from the combustion system are in the form of carbon monoxide gas or CO. One of the technologies in the industrial sector that can observe gas leaks and air quality in industrial areas is the Wireless Sensor Network technology. Wireless Sensor Networks are a set of nodes that are arranged in a wireless network to monitor the surrounding environment and able to communicate with each other through protocols, one of which is Bluetooth Low Energy. Compare to the other protocols, there are some advantages that Bluetooth Low Energy has such as better power savings, being able to send data quickly, easy configuration, and a wide coverage. Therefore, the researcher decided to conduct a research by applying Bluetooth Low Energy in real life, by observing temperature, humidity, CH4 gas and CO gas levels. Through Bluetooth Low Energy, Raspberry Pi is able to send observations to the clients. In this study, two scenarios are used to test the delivery performance of Bluetooth Low Energy. The scenarios are changes in distance without obstacles and changes in distance with obstacles. The test results showed that the change in distance without obstacles and with obstacles had an average total delay of 0.0752 ms and 0.1587 ms.